2019
DOI: 10.2478/raon-2019-0028
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing disorders after treatment for head and neck cancer

Abstract: Background Dysphagia is a common consequence of treatment for head and neck cancer (HNC). The purpose of the study was to evaluate the prevalence of dysphagia in a group of patients treated for HNC in Slovenia, and to identify factors contributing to the development of dysphagia. Patients and methods One-hundred-nine consecutive patients treated for HNC at two tertiary centers were recruited during their follow-up visits. They fulfilled EORTC QLQ-H&N35 and “Swallowing Disorders after Head and Neck Cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 27 publications
2
58
0
6
Order By: Relevance
“…Dysphagia is common in cerebro-vascular disease affecting 60% of all stroke patients accounting for 1.5 million victims per annum in Europe [ 1 , 2 ]. It is occurring in presbyphagia striking more than one-third of all geriatric patients [ 3 ], in up to the half of all patients with throat and neck cancer after operation [ 4 ] radiation or chemotherapy [ 5 ], in non-cancer surgery [ 6 ], in intensive care patients suffering from critical illness neuropathy [ 7 ] and children with aerodigestive disorders [ 8 ]. The economic burden is excessively high, e.g., resulting in additional cost of more than 6000 US$ per hospital case in the United States [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dysphagia is common in cerebro-vascular disease affecting 60% of all stroke patients accounting for 1.5 million victims per annum in Europe [ 1 , 2 ]. It is occurring in presbyphagia striking more than one-third of all geriatric patients [ 3 ], in up to the half of all patients with throat and neck cancer after operation [ 4 ] radiation or chemotherapy [ 5 ], in non-cancer surgery [ 6 ], in intensive care patients suffering from critical illness neuropathy [ 7 ] and children with aerodigestive disorders [ 8 ]. The economic burden is excessively high, e.g., resulting in additional cost of more than 6000 US$ per hospital case in the United States [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include dysphagia (swallowing difficulties), xerostomia (dry mouth), dysgeusia (taste disturbances), and trismus (reduced mouth opening) [8]. The negative effects of eating problems on quality of life (QOL) and everyday life in patients treated for HNC have been documented in quantitative [8][9][10][11][12][13] and qualitative [5,[14][15][16][17][18][19] studies. Based on existing studies [4-7, 18, 20, 21] it is suggested that appropriate rehabilitation services can strengthen the patient's ability to cope with eating problems and thereby reduce the negative consequences.…”
Section: Introductionmentioning
confidence: 99%
“…The gustatory function in general directly influences and is influenced by the person's feeding and nutrition process (8) . Changes in taste can trigger loss of appetite, poor nutrition, and even malnutrition, having in the alternative enteral feeding route its cause (if prolonged use is needed due to dysphagia) or consequence (due to malnutrition, when the person refuses to feed orally).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in gustatory function resulting from the oncological treatment usually take place after radiotherapy (6,7,8) . However, head and neck tumors, due to the anatomical location of the lesion, can themselves trigger significant changes in feedingrelated functions, including taste (9) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation